Optimal Screening Approaches - Coordinating Optimal Screening Programs in Canada: A Multifacted Approach - Chen, Eric; Qamar, Hamza (The Meducator, 2014)
Disease screening is the process of testing asymptomatic individuals for the risk or presence of disease. However, the advent of advanced screening technologies in recent decades poses a challenge to the Canadian health system. The lack of a consistent screening policy among Canadian provinces and poor adherence to screening guidelines have compounded the challenge. The McMaster Health Forum convened a stakeholder dialogue on October 17, 2013 with regards to supporting optimal screening practices in Canada. In consultation with stakeholders, the Forum created an issue brief describing the problem, three elements of a comprehensive approach to address this problem, and key implementation considerations for this approach.